Fidelity Assessment of the Treatnet family (TF): A family-based intervention for adolescents with substance use disorders and their families. (December 2021) - Busse, Anja; Kashino, Wataru; Suhartono, Sanita; Narotama, Narendra; Campello, Giovanna; Irwanto,; Pelupessy, Dicky; Piercy, Fred P.; Essau, Cecilia A.
Highlights: There was a high level of agreement between practitioners' and supervisors' ratings on the practitioner's use of family-based therapeutic skills. In working with adolescents who are affected by substance use disorders, the practitioners showed very good adherence to the Treatnet Family approach. There was a good level of agreement between the adolescents and their family member in terms of how interactive they found the Treatnet Family session. Abstract: Introduction: In transporting family-based interventions to community settings, establishing and maintaining fidelity to intervention is important. This exploratory study was implemented in the framework of a United Nations Office on Drugs and Crime (UNODC) global programme on Drug Dependence Treatment and Care. It is the first to examine an evidence-informed family-based intervention ("Treatnet Family"; TF) adherence for the treatment of adolescents with substance use disorders (SUD) among practitioners in community settings in Jakarta, Indonesia. Method: Twenty-three practitioners at five community-based counselling centres were trained in Treatnet Family and delivered it to 19 adolescents with SUD and their family members over a 6-week period. One of the five local Treatnet Family-trained supervisors randomly selected one session of the family-based intervention (TF) and observed the extent to which the practitioner's adhered to the TF manual. Results: According to the supervisors' observation, all the practitioners used the Treatnet Family core skills such as positive reframing, positive relational reframing, perspective taking, relational questions, and going with resistance. There was a high level of agreement between practitioners' and supervisors' rating on the practitioners' use of specific therapeutic skills as measured using the Inventory of Therapy Techniques (ITT). Conclusion: Results suggest that Treatnet Family can be delivered with adherence by practitioners in community-based settings.